2015
DOI: 10.1111/jace.13459
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Thermoelectric Performance in Hierarchical Mesoscopic Oxide Composites of Ca3Co4O9 and La0.8Sr0.2CoO3

Abstract: The natural contradiction in enhancing electrical conductivity and thermopower in thermoelectric oxides makes it hard to improve the performance of a single thermoelectric oxide material. We report a facile method to construct a unique architecture of thermoelectric oxides that is promising to realize a simultaneous improvement of overall electrical conductivity and thermopower. Here, a series of two-phase nanocomposites comprising of Ca 3 Co 4 O 9 (CCO) and La 0.8 Sr 0.2 CoO 3 (LSCO) has been synthesized thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 49 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…For the strategies of achieving high S 2 σ, resonant state doping, band converging, minority carrier blocking, and quantum confinement were designed and developed. For reducing κ, the strategies of nanostructuring, hierarchical architecturing, and nanoprecipitate inducing were successfully adopted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the strategies of achieving high S 2 σ, resonant state doping, band converging, minority carrier blocking, and quantum confinement were designed and developed. For reducing κ, the strategies of nanostructuring, hierarchical architecturing, and nanoprecipitate inducing were successfully adopted.…”
Section: Introductionmentioning
confidence: 99%
“…[9] For the strategies of achieving high S 2 σ, resonant state doping, [10][11][12] band converging, [13][14][15][16] minority carrier blocking, [17,18] and quantum confinement [19][20][21] were designed and developed. For reducing κ, the strategies of nanostructuring, [22][23][24][25] hierarchical architecturing, [26][27][28] and nanoprecipitate inducing [29][30][31] were successfully adopted.Tin selenide (SnSe) is a typical semiconductor with a narrow bandgap of ≈0.9 eV, [32][33][34] making it a good candidate with great potentials for applications in low-cost thermoelectrics. [35][36][37] A remarkable high peak ZT of ≈2.6 at 923 K was reported in the p-type SnSe single crystals, [38] and a relative high ZT of ≈2.2 at 773 K was also achieved from the n-type Bi-doped SnSe single crystals, [39] both along their b-axes.…”
mentioning
confidence: 99%
“…Meanwhile, the thermoelectric efficiency has also been enhanced by using various techniques such as growth of nanowires [2,3], nanocomposites [1,4−6], superlattices [7] and thin films [8]. Bulk nanocomposites has also been reported to reduce thermal conductivity without affecting the electronic transport [5]. Presently, copper chalcogenides are getting more attention due to their simple chemical formula but complex crystal structures [9−12].…”
mentioning
confidence: 99%
“…Through rational manipulation of particle sizes and interfacial effects, it is possible to increase the power factor together with a reduction of the thermal conductivity, thus yielding the enhancement of the thermoelectric activity of composites in comparison with the individual constituents. Supporting this assumption, it has recently been found that hierarchical mesoscopic oxide composites of Ca 3 Co 4 O 9 and La 0.8 Sr 0.2 CoO 3 display enhanced thermopower [12]. However, the experimental observations of interfacial effects still remain elusive.…”
Section: Introductionmentioning
confidence: 99%